PENGARUH LITERASI KEUANGAN TERHADAP KEBERLANGSUNGAN USAHA MIKRO PADA SEKTOR KULINER DI KABUPATEN PURWAKARTA : ANALISIS REGRESI LINIER SEDERHANA - Noval Dwi Sanggar Ramadhan; Artika Sari Devi; Diaz Raditya Junian (Jurnal Manajemen Pendidikan, 2026)
Objective This study empirically examines the effect of financial literacy on business sustainability of micro-scale culinary enterprises in Purwakarta Regency, Indonesia, addressing the gap between the sector's high failure rate and the limited financial-literacy research specific to this micro, semi-informal context. Methods A quantitative associative-causal design used simple linear regression. Structured Likert-scale (1-5) questionnaires were distributed to 105 culinary micro-entrepreneurs selected via Simple Random Sampling with the Lemeshow formula in May 2026. After excluding 12 careless respondents, validity and reliability were confirmed for 93 respondents; a Kolmogorov-Smirnov test then required removing seven outliers, yielding a final sample of 86 respondents analyzed with SPSS 25 (alpha = 0.05). Results The regression equation was Y = 1.838 + 0.611X, with R = 0.897 and R2 = 0.804, indicating that financial literacy explains 80.4% of the variance in business sustainability. The model was significant (F = 344.354, p < 0.001), and financial literacy positively and significantly affected business sustainability (t = 18.557, p < 0.001), supporting the hypothesis. Novelty This study is among the first to isolate the direct effect of financial literacy on business sustainability among micro-scale culinary enterprises in Purwakarta Regency, an informal, semi-urban economy underrepresented in prior research typically conducted in metropolitan settings.